IL-27 receptor signalling restricts the formation of pathogenic, terminally differentiated Th1 cells during malaria infection by repressing IL-12 dependent signals. - Ana Villegas-Mendez; J Brian de Souza; Seen-Wai Lavelle; Emily Gwyer Findlay; Tovah N Shaw; Nico van Rooijen; Christiaan J Saris; Christopher A Hunter; Eleanor M Riley; Kevin N Couper (PLoS Pathogens)
The IL-27R, WSX-1, is required to limit IFN-γ production by effector CD4⁺ T cells in a number of different inflammatory conditions but the molecular basis of WSX-1-mediated regulation of Th1 responses in vivo during infection has not been investigated in detail. In this study we demonstrate that WSX-1 signalling suppresses the development of pathogenic, terminally differentiated (KLRG-1⁺) Th1 cells during malaria infection and establishes a restrictive threshold to constrain the emergent Th1 response. Importantly, we show that WSX-1 regulates cell-intrinsic responsiveness to IL-12 and IL-2, but the fate of the effector CD4⁺ T cell pool during malaria infection is controlled primarily through IL-12 dependent signals. Finally, we show that WSX-1 regulates Th1 cell terminal differentiation during malaria infection through IL-10 and Foxp3 independent mechanisms; the kinetics and magnitude of the Th1 response, and the degree of Th1 cell terminal differentiation, were comparable in WT, IL-10R1⁻/⁻ and IL-10⁻/⁻ mice and the numbers and phenotype of Foxp3⁺ cells were largely unaltered in WSX-1⁻/⁻ mice during infection. As expected, depletion of Foxp3⁺ cells did not enhance Th1 cell polarisation or terminal differentiation during malaria infection. Our results significantly expand our understanding of how IL-27 regulates Th1 responses in vivo during inflammatory conditions and establishes WSX-1 as a critical and non-redundant regulator of the emergent Th1 effector response during malaria infection.